2012
DOI: 10.7314/apjcp.2012.13.6.2931
|View full text |Cite
|
Sign up to set email alerts
|

Information Sources for Serbian Women on Cervical Carcinoma Risk Factors

Abstract: Background: The epidemiological situation regarding cervical carcinoma in Serbia is rather unfavorable and one of contributing factors is the insufficient interest of women concerning the risk factors responsible for occurrence of this disease. The aim of this study was to determine the sources of relevant information for women Methods: An anonymous questionnaire was used for questioning of patients, students and women undergoing systematic examinations. There were 600 women in total in 2006, 2009 and 2010, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The most frequently chosen source was the media with, 1011 students answering that this source contributed to their knowledge on the subject. Likewise, in another Serbian study, participating females identified the media as the main source of information about CC risk factors [40]. This is a substantial change from previously reported results that the media is a "poor source of comprehensive information on cervical cancer" [41].…”
Section: Discussionmentioning
confidence: 88%
“…The most frequently chosen source was the media with, 1011 students answering that this source contributed to their knowledge on the subject. Likewise, in another Serbian study, participating females identified the media as the main source of information about CC risk factors [40]. This is a substantial change from previously reported results that the media is a "poor source of comprehensive information on cervical cancer" [41].…”
Section: Discussionmentioning
confidence: 88%
“…Conversely, to Magda study in which only 21.9% of female at health Science College (Saudi Arabia) knew about the Human Papilloma Virus vaccine. Some other work from Pakistan showed awareness less than 10% about the Human Papilloma Virus vaccine [16,17]. Opposite to all a recent written report done at Korean University female undergraduate students shows, scholars that mostly informed about Human Papilloma Virus vaccine as primary preventive measures against cervical cancer (83.8%) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Women afraid of the Pap testing finding have greater probability to develop premalignant cervical changes. Many studies have shown that good communication with health professionals is an important factor that influence women's decision for preventive examination (Vivilaki et al, 2005;Matejic et al, 2008;Dugandzija et al, 2012). Role of nurses and midwives in prevention of the cervical cancer is also important (Duval et al, 2009;Gottvall et al, 2009;Kent et al, 2010).…”
Section: Discussionmentioning
confidence: 99%